Improved livestock management in Lower Nyando, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa regional program has selected six sites to test interventions that address risks related to climate change and variability. The aim is to help farmers adapt to climate change, while reducing agriculture related emissions and improve livelihoods through climate smart agriculture interventions. In this case, farmers have acquired improved livestock breeds such as gala goats and doper sheep that are early maturing, easy to manage with high milk productivity thereby increasing their resilience to climate change. Featured here is the Lower Nyando site, in Kenya. Photo: K. Trautmann. Please credit accordingly.